Single Dose Comparative Bioavailability Study of Lisdexamfetamine Dimesylate as Oral Solution Versus Reference Hard Capsules in Healthy Volunteers - Rizea-Savu, Simona; Duna, Simona Nicoleta; Panagiotopoulos, Dimitrios; Sandulovici, Roxana Colette (Frontiers in Pharmacology, 2022)
Lisdexamfetamine is an inactive prodrug of dexamfetamine that is used for the second-line treatment of attention-deficit/hyperactivity disorder (ADHD) and moderate to severe binge eating disorder (BED). Once in the blood, the prodrug is hydrolyzed in erythrocyte cytosol, thus releasing the active dexamfetamine. We here present a fully validated HPLC-MS/MS analytical method for simultaneous determination of lisdexamfetamine and dexamfetamine in human plasma and the first published comparative bioavailability study of lisdexamfetamine including a GMP finished product formulated as oral solution. The Test (T) / Reference (R) ratios for the geometric means (%) of the primary pharmacokinetic (PK) parameters and their corresponding two-sided 90% confidence intervals (CIs) were contained within the predefined regulatory limits of 80.00% to 125.00% for both lisdexamfetamine and dexamfetamine. While for the lisdexamfetamine prodrug, PK results for the two formulations were slightly different due to the distinct dissolution state at administration, the PK parameters calculated for dexamfetamine were almost identical. A potential explanation of this phenomenon, already described in literature, is that biotransformation of lisdexamfetamine by red blood cells (rather than its release within the gastrointestinal tract) is the process controlling the rate of dexamfetamine delivery.